Complexation of NpO2+ with (2-hydroxyethyl)ethylenediaminetriacetic acid (HEDTA) in aqueous solutions: thermodynamic studies and structural analysis. Issue 115 (9th December 2016) - Li, Xingliang; Zhang, Zhicheng; Martin, Leigh R.; Luo, Shunzhong; Rao, Linfeng
Abstract : The complexation of Np(v ) with HEDTA in aqueous solutions was investigated by spectrophotometry, microcalorimetry and EXAFS. Thermodynamic parameters were determined and coordination modes also discussed. Abstract : Complexation of Np(v ) with N -(2-hydroxyethyl)ethylenediaminetriacetic acid (HEDTA) was studied in aqueous solution ( I = 1.0 mol L −1 NaClO4, t = 25 °C) by spectrophotometry, microcalorimetry and Extended X-ray absorption fine structure (EXAFS) spectroscopy. Equilibrium constants for the formation of three complexes, NpO2 L 2−, NpO2 (HL) −, and (NpO2 )2 (OH)2 L2 6−, were determined to be (6.91 ± 0.06), (4.28 ± 0.03) and −(4.93 ± 0.03), respectively. The enthalpies of complexation were determined to be −(8.0 ± 2.0) kJ mol −1 for NpO2 L 2− and −(2.2 ± 2.0) kJ mol −1 for NpO2 (HL) − . Thermodynamic data of the complexation of Np(v ) with HEDTA were compared to those of Np(v ) with other aminopolycarboxylic acids, gaining insight into the possible coordination modes of the complexes. The EXAFS studies provided further structural information on those modes. In both NpO2 L 2− and NpO2 (HL) − complexes, HEDTA coordinates to Np(v ) in a tridentate mode through two oxygens of two carboxylic groups and one nitrogen of the amine group. In the (NpO2 )2 (OH)2 L2 6− complex, two Np(v ) atoms are bridged by two hydroxides and each HEDTA maintains the tridentate coordination mode.